A reader on reading - Manguel, Alberto (New Haven [Conn.] : Yale University Press, 2010)
A collection of essays from Alberto Manguel, an Argentine-born Canadian author, in which he discusses his views on literature and the activity of reading.
A reader in the looking-glass wood -- Room for the shadow -- On being Jewish -- Meanwhile, in another part of the forest -- The further off from England -- Homage to Proteus -- Borges in love -- Borges and the longed-for Jew -- Faking it -- The death of Che Guevara -- The blind bookkeeper -- The perseverance of truth -- AIDS and the poet -- The full stop -- In praise of words -- A brief history of the page --The voice that says "I" -- Final answers -- What song the sirens sang -- Notes towards a definition of the ideal reader -- How Pinocchio learned to read -- Candide in Sanssouci -- The gates of paradise -- Time and the doleful knight -- Saint Augustine's computer -- Reading white for black -- The secret sharer -- Honoring Enoch Soames -- Jonahand the whale -- The legend of the dodos -- In memoriam -- God's spies -- Once again, Troy -- Art and blasphemy -- At the mad hatter's table -- Notes towards a definition of the ideal library -- The library of the wandering Jew -- The library as home -- The end of reading.
Includes bibliographical references (p. 294-296) and index.
Library Journal
Pub Weekly
Library Journal, March 2010
Pub Weekly, February 2010
Adult.
Keywords: Manguel, Alberto -- Books and reading; Manguel, Alberto -- Books and reading; Books and reading; Books and reading